2018
DOI: 10.1016/j.jneuroim.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Low amounts of bisecting glycans characterize cerebrospinal fluid-borne IgG

Abstract: Immunoglobulin G (IgG) harbors a conserved N-glycosylation site which is important for its effector functions. Changes in glycosylation of IgG occur in many autoimmune diseases but also in physiological conditions. Therefore, the glycosylation pattern of serum IgG is well characterized. However, limited data is available on the glycosylation pattern of IgG in cerebrospinal fluid (CSF) compared to serum. Here, we report significantly reduced levels of bisected glycans in CSF IgG. Galactosylation and sialylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Elevated bisecting GlcNAc and reduced galactosylation are known to enhance IgG effector functions; however elevated core fucosylation has the opposite effect. Nonetheless, another recent study conversely observed that IgG from CSF of MS patients is characterized by significantly reduced bisecting GlcNAc [ 19 ], confounding the previous observations. Conversely, all glycosylation changes observed herein are jointly suggesting the enhanced proinflammatory potential of the circulating IgG.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Elevated bisecting GlcNAc and reduced galactosylation are known to enhance IgG effector functions; however elevated core fucosylation has the opposite effect. Nonetheless, another recent study conversely observed that IgG from CSF of MS patients is characterized by significantly reduced bisecting GlcNAc [ 19 ], confounding the previous observations. Conversely, all glycosylation changes observed herein are jointly suggesting the enhanced proinflammatory potential of the circulating IgG.…”
Section: Discussionmentioning
confidence: 92%
“…Research studies focused on alterations of IgG or total plasma protein N-glycome in MS are scarce. One study examined IgG glycosylation pattern in cerebrospinal fluid (CSF) [ 19 ], while another tackled MS-related IgG1 glycosylation changes in serum and CSF [ 20 ]. In general, the presence of oligoclonal IgG in CSF is considered to be a hallmark of MS [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lectin-ELISA testing of the α1,6-fucosyl core residue (core fucose) of N-glycan of IgG immunoglobulins was performed using AAL lectin. The principle of the validated test [3,7,14] is demonstrated in the insert of Fig. 2, a. Localization of the detected glycan in the IgG molecule can be ascertained from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…N-glycan residues attached to asn297 of the immunoglobulin IgG molecule are responsible for changing itsstructuralconformationandareusedasmarkersofmanyinflammatorydiseases. Freezingstabi introduction Glycosylation of IgG (both native and artificially produced pharmaceutical monoclonal formulations [most are IgG]) has become an intensely growing "hot topic" in biomedical and pharmaceutical sciences [1], with studies of IgG glycans used to discriminate clinical conditions [2] and identify their roles in specific neurological conditions [3]. N-glycan residues attached to Asn297 of the IgG molecule are responsible for changing its structural conformation and subsequently the affinity towards pro-and anti-inflammatory receptors on effector cells [4].…”
mentioning
confidence: 99%
“…To characterize the glycosylation of IgG Fc, we additionally employed Liquid chromatography-electrospray ionization mass spectrometry (LC-ESI-MS). Total IgG was purified from serum using Protein G Sepharose (GE Healthcare, Chicago, IL, USA) and the IgG eluates were digested with sequencing grade modified trypsin (Promega) overnight at 37 • C. The IgG peptides were then analyzed for specific Fc-glycans as described in Knopf et al [71]. Briefly, detected mass spectra were analyzed for the typical retention times of IgG1, IgG2 and IgG3 glycopeptides using the Compass DataAnalysis software V5.0 (Bruker, Billerica, MA, USA) and specific glycans were extracted from the data using LaCyTools [72].…”
Section: Lc-esi-ms Analyses Of Igg Fc Glycosylationmentioning
confidence: 99%